Correlation network analysis between phenotypic and genotypic traits of chili pepper - Silva, Anderson Rodrigo da; Rêgo, Elizanilda Ramalho do; Pessoa, Angela Maria dos Santos; Rego, Mailson Monteiro do (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to build weighted correlation networks, in order to discover correlation structures and link patterns among 28 morphoagronomic traits of chili pepper related to seedling, plant, inflorescence, and fruit. Phenotypic and genotypic information of 16 Capsicum genotypes were analyzed. Correlation structures and link patterns can be easily identified in the matrices using the Fruchterman‑Reingold algorithm with correlation network information. Both types of correlations showed the same general link pattern among fruit traits, with high broad-sense heritability values and high aptitude of the genotypes for agronomic and ornamental breeding. Leaf dimensions are correlated with a cluster of fruit traits. Correlation networks of chili pepper traits may increase the effectiveness of genotype selection, since both correlated traits and groups can be identified.